2005
DOI: 10.1016/j.femsle.2004.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Construction and characterization of a live, attenuated apxIICA inactivation mutant ofActinobacillus pleuropneumoniaelacking a drug resistance marker

Abstract: The apxIIC gene of Actinobacillus pleuropneumoniae serotype 7 was inactivated by homologous recombination using a sucrose counter-selectable marker system, resulting in a mutant strain that had no antibiotic resistance marker and expressed an inactivated ApxII toxin. The safety and immunogenicity of the mutant were evaluated in mice. The mutant strain caused no adverse effects in mice at doses up to 2 x 10(9) CFU via the intraperitoneal route while the parental strain induced total mortality at a dose of 2 x 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…A live vaccine is considered to offer a better prospect of obtaining crossserovar protection against A. pleuropneumoniae serovars or H. parasuis, and live attenuated deletion mutants have been shown to be effective in controlling infection by A. pleuropneumoniae (24,25). Based on the observation of cross-protection of SLW03 against heterologous A. pleuropneumoniae infection in recovery pigs, we constructed SLW05.…”
Section: Discussionmentioning
confidence: 99%
“…A live vaccine is considered to offer a better prospect of obtaining crossserovar protection against A. pleuropneumoniae serovars or H. parasuis, and live attenuated deletion mutants have been shown to be effective in controlling infection by A. pleuropneumoniae (24,25). Based on the observation of cross-protection of SLW03 against heterologous A. pleuropneumoniae infection in recovery pigs, we constructed SLW05.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant ApxI and ApxII were purified following overexpression of the genes apxICA and apxIICA in an expression vector. The C gene was expressed along with the structural A gene as it is necessary for the maturation of the protoxin in an active form (Thumbikat et al ., 2003; Bei et al ., 2005). As insufficient amounts of proteins were recovered in the soluble fraction of bacterial lysates, recombinant toxins were purified from inclusion bodies as denaturated proteins, renaturated in an arginine‐containing buffer, and exchanged against phosphate buffer.…”
Section: Resultsmentioning
confidence: 99%
“…It is generally accepted that live attenuated vaccine of A. pleuropneumoniae can elicit both humoral and cell‐mediated immune responses and this may be exploited for A. pleuropneumoniae prophylaxis. Numerous mutants have been constructed and tested as live attenuated vaccines for their protective efficacy 8,11,12,13,14,34. Our previous work revealed that the double ΔapxIC/ΔapxIIC mutant of A. pleuropneumoniae serotype 1 (SLW03) secreted inactivated forms of both ApxI and ApxII, and pigs vaccinated via intranasal route were completely protected against a cross‐serotype challenge with serotype 9 strain of A. pleuropneumoniae 26.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of the disease is multifactorial with RTX toxins, outer membrane proteins, capsule, lipopolysaccharide and urease all contributing to virulence 5–7. Attenuated live vaccine or subunit vaccines using virulence factor elicit an effective immune response and provide protection against A. pleuropneumoniae infection 8–17. Live vaccines with foreign immunogenes elicit cellular immune responses and mucosal immunoglobulin A antibody.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation